Enhanced Mitochondrial Transient Receptor Potential Channel, Canonical Type 3–Mediated Calcium Handling in the Vasculature From Hypertensive Rats - Wang, Bin (J Am Heart Assoc, 2017)
BACKGROUND: Mitochondrial Ca(2+) homeostasis is fundamental to the regulation of mitochondrial reactive oxygen species (ROS) generation and adenosine triphosphate production. Recently, transient receptor potential channel, canonical type 3 (TRPC3), has been shown to localize to the mitochondria and to play a role in maintaining mitochondrial calcium homeostasis. Inhibition of TRPC3 attenuates vascular calcium influx in spontaneously hypertensive rats (SHRs). However, it remains elusive whether mitochondrial TRPC3 participates in hypertension by increasing mitochondrial calcium handling and ROS production. METHODS AND RESULTS: In this study we demonstrated increased TRPC3 expression in purified mitochondria in the vasculature from SHRs, which facilitates enhanced mitochondrial calcium uptake and ROS generation compared with Wistar‐Kyoto rats. Furthermore, inhibition of TRPC3 by its specific inhibitor, Pyr3, significantly decreased the vascular mitochondrial ROS production and H(2)O(2) synthesis and increased adenosine triphosphate content. Administration of telmisartan can improve these abnormalities. This beneficial effect was associated with improvement of the mitochondrial respiratory function through recovering the activity of pyruvate dehydrogenase in the vasculature of SHRs. In vivo, chronic administration of telmisartan suppressed TRPC3‐mediated excessive mitochondrial ROS generation and vasoconstriction in the vasculature of SHRs. More importantly, TRPC3 knockout mice exhibited significantly ameliorated hypertension through reduction of angiotensin II–induced mitochondrial ROS generation. CONCLUSIONS: Together, we give experimental evidence for a potential mechanism by which enhanced TRPC3 activity at the cytoplasmic and mitochondrial levels contributes to redox signaling and calcium dysregulation in the vasculature from SHRs. Angiotensin II or telmisartan can regulate [Ca(2+)](mito), ROS production, and mitochondrial energy metabolism through targeting TRPC3.